Ionic Conduction in Composite Polymer Electrolytes: Case of PEO:Ga-LLZO Composites - Li, Zhuo; Huang, He-Ming; Zhu, Jia-Kun; Wu, Jian-Fang; Yang, Hui; Wei, Lu; Guo, Xin (ACS applied materials & interfaces, 2019)
By dispersing Li6.25Ga0.25La3Zr2O12 (Ga-LLZO) nanoparticles in poly(ethylene oxide) (PEO) matrix, PEO:Ga-LLZO composite polymer electrolytes are synthesized. The PEO: Ga-LLZO composite with 16 vol % Ga-LLZO nanoparticles shows a conductivity of 7.2 × 10–5 S cm–1 at 30 °C, about 4 orders of magnitude higher than the conductivity of PEO. The enhancement of the ionic conductivity is closely related to the space charge region (∼3 nm) formed at the interface between the PEO matrix and the Ga-LLZO nanoparticles. The space charge region is observed by transmission electron microscope (TEM) and corroborated by the phase-field simulation. Using the random resistor model, the lithium-ion transport in the composite polymer electrolyte is simulated by the Monte Carlo simulation, demonstrating that the enhanced ionic conductivity can be ascribed to the ionic conduction in the space charge regions and the percolation of the space charge regions.